2020
DOI: 10.1021/acs.inorgchem.9b03214
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structural and Electronic Properties of Bismuth Trihalides and Related Compounds

Abstract: Bismuth trihalides, BiX 3 (X F, Cl, Br and I) have been thrust into prominence recently due to their close chemical relationship to the halide perovskites of lead, which exhibit remarkable performance as active layers in photovoltaic cells and other optoelectronic devices. In the present work we have used calculations based on density functional theory to explore the energetics and electronic properties of BiX 3 in a variety of known and hypothetical structure types. The results for BiX 3 are compared with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…One factor is certainly the tendency of the Bi(III) compounds to crystallize as low-dimensional 3:2:9 type phases due to their high covalency, with bismuth halide compounds notably favoring layered-type structures. 104 Most of our predictions, however, relate to rare-earth phases, and we believe that the challenges of synthesizing these lanthanide compounds are much greater than those encountered with post-transition metals. In particular, both the starting materials and products are likely to be air-sensitive and require rigorous exclusion of moisture.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…One factor is certainly the tendency of the Bi(III) compounds to crystallize as low-dimensional 3:2:9 type phases due to their high covalency, with bismuth halide compounds notably favoring layered-type structures. 104 Most of our predictions, however, relate to rare-earth phases, and we believe that the challenges of synthesizing these lanthanide compounds are much greater than those encountered with post-transition metals. In particular, both the starting materials and products are likely to be air-sensitive and require rigorous exclusion of moisture.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The case of Cs 2 NaErI 6 , for example, involved a solid state reaction between carefully dried Csl, Nal, Er metal, and I 2 in a sealed tantalum tube, rather than a simple reaction in aqueous solution. The rare earth metal iodides are more ionic than their post-transition-metal analogues, and we would expect their band gaps to be wider than, for example, bismuth-containing compounds . They are therefore less likely to be useful for PV applications and more suitable for use in areas such as X-ray detection and magnetic and optical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, YCl 3 contains (002) planes of octahedral cation voids, in contrast to LYC, which has Y 3+ and Li + ions distributed throughout its (001) and (002) planes. Deng et al 52 recently demonstrated that YCl 3 is amenable to polymorphism, especially with respect to the related BiI 3 -type structure which shows an alternate ABCABC anion stacking arrangement. According to their calculations, the energy difference between the two structure-types is ≈0.1 kJ mol −1 (≈1 meV atom −1 ), suggesting that alternate stackings, or even stacking faults, are possible in YCl 3 -type structures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigations on the synthesis products as a function of the milling conditions (i.e., frequency and time) and the effects of introducing chemical additives to control the kinetics of the crystallization should be conducted to make full use of this synthetic strategy. Another challenge in the solution-based fabrication of such halide double perovskites is that the low-dimensional, non-conductive, 3:2:9 phase (e.g., Cs 3 Bi 2 Br 9 ) is thermodynamically favored, 30 thus competing with the elpasolite phase (i.e., Cs 2 AgBiBr 6 ). The 3:2:9 phase consists of face-sharing double-layered [Bi 2 Br 9 ] 3– octahedra.…”
mentioning
confidence: 99%